Identification and Characterization of Bacterial Lipase from Plateu Soil in West Java - Vivitri Dewi Prasasty; Vinella Winata; Muhammad Hanafi (Research Center for Chemistry - LIPI, 2016)
Lipases are known as glycerol ester hydrolases that catalyze the hydrolysis of triglycerides into free fatty acids and glycerol. Lipases are found in human, animal, plant, and microorganisms. The aim of this research is to identify lipase producers and characterize bacterial lipase from West Java plateau soil. Plateau soil bacteria samples were isolated on lipase screening medium containing Rhodamine B. Olive oil was used as a substrate in screening and production medium bacterial lipases. From 16 bacterial isolate of lipase producers, 14 were identified as Bacillus sp. and the others were identified as Pseudomonas alcaligenes. All isolates were taken into production step to determine their lipase activities. Moreover, top 3 lipase activities out of 16 lipase activities were chosen to find the optimum pH and temperature. Both characterizations showed pH optimum and temperature optimum from each lipase. These optimum condition were used in heat stability characterization for each lipase samples. The result showed that lipase from isolate COK 2 in optimum pH 4 and temperature 50oC was the most stable lipase due to this sample has good and stable activity for 1 to 5 hours incubation time. Lipase sample from isolate COK 2 has good efficiency for lipase productivity in acid condition and high temperature. Results of this investigation could encourage utilization of these activity enhancers for various industrial applications.